Creditability of Cardiac Biomarkers in Sudden Cardiac Death - Tamara Ablahad Hanna; Muataz A. AL-Qazzaz (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Natural deaths constitute a significant portion of total deaths cases received for autopsy ingeneral. Cardiovascular system occupies the vast majority of natural death causes. Sudden cardiac deathis a catastrophic complication of a number of cardiovascular diseases and affect all ages. Death is mostlyunexpected and has a devastating impact on both the surviving family and community. Clinicians use cardiacmarkers, highly sensitive and specific for detection of myocardial damage to screen living patients for acutemyocardial infarction (AMI), however to that point, the utility of those markers for diagnosis of cardiacdeath in autopsy setting has not been fully established. Materials and Methods: A prospective postmortemcase control study was carried out on 103 medico-legal cases referred to the Medico-Legal directorate inBaghdad during 6 months period in 2020. The cases under study were classified in to two groups, those dieddue to cardiac causes (53) as cases group, and those died due to traumatic causes (50) as control group. Bloodsamples were collected using disposable syringes to withdraw 3-5ml of blood then immediately centrifugedto separate the serum and stored at -20°C till biochemical analysis for cardiac biomarkers (High sensitivetroponin I, MB fraction of Creatin kinase and Lactate dehydrogenase). Results: Males constituted 77%from the total number while females constituted 23%. The mean age of the total study group was 42.57±15.125 years with a range between 11-72 years. The total number of cases group were 53 case( 77% maleand 23% female) with a mean age of 48.89±12.566, compared with 50 cases as controls group from the totalnumber(76%male and 24% female) with mean age of 35.88±14.825. Sensitivity of High sensitive troponinI was 96.2% which was acceptable and it’s specificity for diagnosis of sudden cardiac causes of death was22% which was very low. While Sensitivities of MB fraction of Creatin kinase and Lactate dehydrogenasewere 96.2% and 94.3% respectively and their specificities were 6% and 14% respectively. There were nocorrelations between post mortem interval and all three biochemical parameters levels. Conclusion: Highsensitive troponin I, MB fraction of Creatin kinase and Lactate dehydrogenase were not reliable as diagnosticbiomarkers for sudden cardiac deaths without gross postmortem and histopathological examination. Therewere no correlations between the three biomarkers (High sensitive troponin I, MB fraction of Creatin kinaseand Lactate dehydrogenase) and the post mortem interval .